Menganalisis Program Kinerja pada Laporan Keuangan Pemerintah Daerah Kabupaten dan Kota Serang : Studi Kabupaten dan Kota Serang 2017-2021 - Lawe Anasta; Vidia Ambarwati (Reviu Akuntansi, Manajemen, dan Bisnis, 2023)
Purpose: Purpose: This study aims to prove, analyze, and determine how to compare the financial performance of the Regional Governments of the Regency and City of Serang for 2017-2021. Methodology/Approach: This study used secondary data by taking data from the BPK Central Office. Results of the 2017-2021 Regional Government Financial Reports for Serang Regency and City with a total of 10 Financial Statements for each local government. The sampling in this study used the Financial Statements of the Regional Government of the Regency and City of Serang. Data were analyzed using a Financial Ratio analysis. Results/findings: The results of the study show that the financial ratios used to measure the financial performance of the Regional Government of the Regency and City of Serang, with a comparison to the Regency of Serang and the City of Serang which have differences in terms of Financial Ratios and can be measured by Financial Ratio Analysis so that you can find out the performance of the Regional Government of Serang Regency and Serang City, the results of this study Serang Regency and Serang City have quite good performance in terms of their Financial Statements.